Clinical evaluation of colony-stimulating factor 1 receptor inhibitors. (April 2021) - Ordentlich, Peter
Abstract: Signaling through colony-stimulating factor 1 receptor (CSF1R) regulates the development, differentiation, and activation of mononuclear phagocytic cells. Inhibition of this pathway provides an opportunity for therapeutic intervention in diseases in which these cells play a pathogenic role, including cancers, inflammation, fibrosis, and others. Multiple monoclonal antibodies and small molecule inhibitors targeting CSF1R or its known ligands CSF1 and IL-34 have been clinically tested and are generally well tolerated with side effects associated with on-target macrophage inhibition or depletion. To date, clinical activity of CSF1R inhibitors has been primarily observed in diffuse-type tenosynovial giant cell tumors, a disease characterized by genetic alterations in CSF1 leading to dysregulated CSF1R signaling. Expanded development into novel indications such as chronic graft vs host disease may provide new opportunities to further explore areas where a role for CSF1R dependent monocytes and macrophages has been established. This review presents key findings from the clinical development of 12 CSF1/CSF1R targeted therapies as monotherapy or in combination with immune checkpoint inhibitors and chemotherapy.